GAYA KEPEMIMPINAN DAN PERAN HUMAN CAPITAL PADA LEMBAGA PENDIDIKAN - Riza Mahara, Riza Mahara (Yayasan Darul Hasanah Aceh, 2024)
In the middle of globalization and digital transformation, education institution face complex challenges that require adaptive and quality leadership strategies, with human capital as a strategic asset that determines the organization's competitive advantage. Technological changes, global competition, and efficiency needs encourage companies to develop a more comprehensive and dynamic leadership approach, which focuses on developing human resource capabilities through the integration and development of internal talent potential. This research uses a literature review or literature review related to the steps of implementing commitment to effectiveness in the company. This research uses qualitative research methods, where the study is used consistently with methodological assumptions. By collecting some relevant literature, it can be said that this research is exploratory.